Public Service Responsiveness and Reliability on Public Satisfaction: A Study at the Dompu Subdistrict Government Office, Indonesia - Amelia Catur Pratiwi; Nurul Hayat; Rizky Ramadhan (Advances in Management & Financial Reporting, 2026)
Purpose: This study aims to evaluate and analyze the effect of responsiveness and reliability of public services on public satisfaction with the Dompu Subdistrict Government. The study hypothesizes that both responsiveness and reliability have a positive and significant influence on public satisfaction. Research Method: This study used a quantitative approach with an explanatory research design. Primary data were collected through questionnaires distributed to 60 service users at the Dompu Subdistrict Government, selected using purposive sampling. The research variables were responsiveness and reliability as independent variables, and public satisfaction as the dependent variable. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Results and Discussion: The findings show that responsiveness and reliability have a positive and significant effect on public satisfaction. Reliability, particularly data accuracy and consistency of service procedures, was found to be the more dominant factor compared with responsiveness. Together, responsiveness and reliability explain 64.7% of the variation in public satisfaction. Implications: The results indicate that improving public satisfaction requires synergy between responsive service delivery and accurate, consistent administrative performance. Future studies are recommended to include other dimensions of service quality to provide a more comprehensive understanding of factors affecting public satisfaction. Originality: This study provides empirical evidence on the dominant role of reliability in shaping public satisfaction within subdistrict-level public services, specifically in the Dompu Subdistrict Government.